Prevalence, quantification and isolation of pathogenic shiga toxin Escherichia coli O157:H7 along the production and supply chain of pork around Hubei Province of China. (February 2018) - Khan, Sher Bahadar; Zou, Geng; Xiao, Ran; Cheng, Yuting; Rehman, Zia Ur; Ali, Sher; Memon, Atta Muhammad; Fahad, Shah; Ahmad, Irshad; Zhou, Rui
Abstract: Shiga toxin Escherichia coli (STEC) O157:H7 is an important zoonotic food borne pathogen causing gastroenteritis that may lead to life threatening hemorragic colitis (HC) and hemorrhagic uremic syndrome (HUS). 325 meat and tissue samples were tested for enumeration of O157:H7 strains using most probable number (MPN)-PCR targeting their specific genes flicH7 and rfbO157 followed by isolation, sereotyping and pathogenicity testing. The overall prevalence of O157:H7 was 41.3% (134/325) along the production and supply chain of pork (PSCP), being higher in supply chain (59%, 118/200) as compared to pig farms (12.8%, 16/125). Along the PSCP, the highest prevalence was found in slaughter houses (86.25%, 69/80) followed by wet- (53.3%, 32/60) and super-markets (28.3%, 17/60). The MPN values ranged from 3 to 1100 MPN/g in overall positive samples, being higher in slaughter houses followed by wet and super markets. Except from intestine and meat samples of slaughter house, the MPN was found higher in summer as compared to winter samples. Eight STEC O157:H7 isolated from meat and liver samples were tested in Balb/C mice for pathogenicity. After development of clinical signs and symptoms, 50–83.3% mortality was produced in the infected mice. Histopathological investigations revealed visible necrosis of intestinal epithelial cells, shedding of cellular debris in the intestine, while in the kidney, necrosis of renal cortical portion of tubular epithelial cells was observed. STEC O157:H7 is prevalent along PSCP around Hubei of China in different proportions being alarmingly higher in supply chain and markets which is a matter of concern for public health. Highlights: STEC O157:H7 is prevalent along PSCP around Hubei province of China in different proportions being alarmingly higher in supply chain and markets which is a matter of concern for public health. The overall prevalence of E. coli O157:H7 was 41.3% (134/325) along PSCP, being higher in supply chain (59%, 118/200) as compared to pig farms (12.8%, 16/125). Along the supply chain, the highest prevalence was found in slaughter houses (86.25%, 69/80) followed by wet (53.3%, 32/60) and super markets (28.3%, 17/60). High mortality with prominent histopathological changes were observed in mice administered with the strain having both Stx1 and Stx2.